Does reversible cysteine oxidation link the Western diet to cardiac dysfunction?. Issue 5 (27th January 2014) - Behring, Jessica B.; Kumar, Vikas; Whelan, Stephen A.; Chauhan, Pratibha; Siwik, Deborah A.; Costello, Catherine E.; Colucci, Wilson S.; Cohen, Richard A.; McComb, Mark E.; Bachschmid, Markus M.
ABSTRACT: Using a novel cysteine thiol labeling strategy coupled with mass spectrometric analysis, we identified and quantified the changes in global reversible cysteine oxidation of proteins in the left ventricle of hearts from mice with metabolic syndrome‐associated diastolic dysfunction. This phenotype was induced by feeding a high‐fat, high‐sucrose, type‐2 diabetogenic diet to C57BL/6J mice for 8 mo. The extent of reversible thiol oxidation in relationship to the total available (free and reducible) level of each cysteine could be confidently determined for 173 proteins, of which 98 contained cysteines differentially modified ≥1.5‐fold by the diet. Our findings suggest that the metabolic syndrome leads to potentially deleterious changes in the oxidative modification of metabolically active proteins. These alterations may adversely regulate energy substrate flux through glycolysis, β‐oxidation, citric acid (TCA) cycle, and oxidative phosphorylation (oxphos), thereby contributing to maladaptive tissue remodeling that is associated with, and possibly contributing to, diastolic left ventricular dysfunction.—Behring, J. B., Kumar, V., Whelan, S. A., Chauhan, P., Siwik, D. A., Costello, C. E., Colucci, W. S., Cohen, R. A., McComb M. E., Bachschmid, M. M. Does reversible cysteine oxidation link the Western diet to cardiac dysfunction? FASEB J . 28, 1975–1987 (2014). www.fasebj.org